Treatment of Textile Effluent by Natural Coagulants in Erode District - Muralimohan, N.; Palanisamy, T. (Asian Journal of Chemistry, 2014)
A preliminary investigation was carried out for the feasible use of natural coagulants for the treatment of textile waste water in Erode district of Tamil Nadu (India). In this paper, different natural coagulants like Moringa oleifera, Tamarina indica, Strychonomous potatorum of 10, 20, 40, 60 and 80 mL dosages were used to spot the suitable one as primary coagulant. Floc formation in coagulation process had been studied in the laboratory scale to determine the optimum dosage of natural coagulants. Pre and post treated textile wastewaters with natural coagulants were considered to evaluate the percentage removal efficiency on the major pollutants of concern in textile effluent such as pH, turbidity, TSS, TDS, COD and BOD. From the observed results, the natural coagulant Moringa oleifera gives better removal efficiencies with respect to turbidity, TSS, TDS, COD and BOD and appears to be suitable for textile effluent treatment in Erode district, when compared with Tamarina indica and Strychonomous potatorum.